2022
DOI: 10.1101/2022.01.27.478034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An organoid CRISPRi screen revealed that SOX9 primes human fetal lung tip progenitors to receive WNT and RTK signals

Abstract: The balance between self-renewal and differentiation in human fetal lung epithelial progenitors controls the size and function of the adult organ. Moreover, progenitor cell gene regulation networks are employed by both regenerating and malignant lung cells, where modulators of their effects could potentially be of therapeutic value. Details of the molecular networks controlling human lung progenitor self-renewal remain unknown. We performed the first CRISPRi screen in primary human lung organoids to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…The SOX9 - cells in these organoids stopped proliferating (Fig. 7A), consistent with our recent findings (Sun et al, 2022) and we could not maintain these organoids for subsequent passages. Moreover, we observed altered E-cadherin patterning and F-actin in the SOX9 - cells (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The SOX9 - cells in these organoids stopped proliferating (Fig. 7A), consistent with our recent findings (Sun et al, 2022) and we could not maintain these organoids for subsequent passages. Moreover, we observed altered E-cadherin patterning and F-actin in the SOX9 - cells (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Such observations have led us to reason that the three RTK inputs in the SN medium also show combinatorial effects on the cells. For example, our recent findings have suggested that the three RTK inputs contributed to the expression of ETV4 and ETV5, co-regulators of SOX9 in the self-renewing tip epithelial cells (Sun et al, 2022). Moreover, we speculate that similar crosstalk occurs in vivo where the RTK ligands cooperate and contribute to development.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SOX9 is regulated and maintained by the Wnt/β-catenin signalling pathway, as supported by many studies (Blache et al, 2004;Snowball et al, 2015;Liang et al, 2022;Liu et al, 2022;Sun et al, 2022). In tracheal cartilage and human lung bud tip progenitors, the elevation of either the WNT protein or Wnt signalling pathway amplifier enhanced the expression of SOX9 and maintained its level in the cell nucleus (Nasr et al, 2021;Hein et al, 2022).…”
Section: The Wnt Signalling Pathway Regulates the Expression Of Sox9mentioning
confidence: 86%
“…The findings of ChIP-sequencing demonstrated that SOX9 bound to the enhancers of Fzd8 and Sox4 and promoted their transcription in intestinal stem cells (ISCs) (Huang et al, 2017). In lung tip progenitors, SOX9 directly upregulated the transcription of LGR5 and CD44, which are the amplifiers of the Wnt signalling pathway (Sun et al, 2022). Moreover, SOX9 was also reported to bind the promoter of ubiquitin-specific peptidase 22 (USP22), a deubiquitinating enzyme, promote its transcription, and activate the Wnt/β-catenin pathway (Miao et al, 2022).…”
Section: Sox9 Activates the Canonical Wnt Signalling Pathwaymentioning
confidence: 99%
“…One advantage is that these systems represent 3D models of human development. A CRISPRi screen has been applied to an organoid model, identifying key TFs in fetal lung development through perturbation of select promoters ( Sun et al, 2022 ). Similar 3D systems could be used to study the role of enhancers in developmental disease.…”
Section: Introductionmentioning
confidence: 99%